NEEDS ANALYSIS OF ESP FOR INDONESIAN HAJJ OFFICERS - Rezky Atri Oktarin; Tania Syafutri; Adi Saputra (Swakarya: Jurnal Penelitian Sosial dan Pengabdian Masyarakat, 2025)
This study aims to identify the specific English language needs of key stakeholders involved in Hajj and Umrah services, including former Hajj officers, language trainers, and employees of Hajj–Umrah travel agencies. As English increasingly becomes a crucial medium for facilitating international mobility and assisting pilgrims from diverse linguistic backgrounds, a systematic needs analysis is necessary to design an effective English for Specific Purposes (ESP) curriculum tailored to the operational demands of pilgrimage services. This research employs a mixed-methods design combining quantitative surveys and qualitative interviews. A total of 60 respondents participated in the questionnaire, while nine participants representing the three stakeholder groups were involved in semi-structured interviews. Quantitative data were analyzed using descriptive statistics, whereas qualitative data were examined through thematic coding. The findings indicate that the most essential English competencies include communicating safety information, assisting pilgrims during airport and immigration procedures, providing hotel and transportation explanations, and managing emergency situations. Despite acknowledging the importance of English proficiency, many respondents reported limited mastery of functional vocabulary, insufficient exposure to real-world communication scenarios, and a lack of structured training aligned with their professional duties. The study reveals a strong need for practical ESP materials emphasizing situational dialogues, role-plays, task-based activities, and context-specific vocabulary lists. These results suggest that a specialized and operationally relevant ESP curriculum is necessary to enhance the linguistic readiness of Hajj and Umrah personnel. The study contributes to the literature by offering empirical evidence and proposing pedagogical implications for institutions and policymakers responsible for professional training in pilgrimage services.